Outcomes for symptomatic non-obstructed individuals and individuals with mild (GOLD stage 1) COPD in a population based cohort - Perez-Padilla, Rogelio (Int J Chron Obstruct Pulmon Dis, 2018)
BACKGROUND: We aimed to study the adverse outcomes of symptomatic and asymptomatic non-obstructed individuals and those with mild COPD longitudinally in participants from three Latin-American cities. METHODS: Two population-based surveys of adults with spirometry were conducted for these same individuals with a 5- to 9-year interval. We evaluated the impact of respiratory symptoms (cough, phlegm, wheezing or dyspnea) in non-obstructed individuals, and among those classified as Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage 1, COPD on exacerbation frequency, mortality and FEV(1) decline, compared with asymptomatic individuals without airflow obstruction or restriction. RESULTS: Non-obstructed symptomatic individuals had a marginal increased risk of mortality (HR 1.3; 95% CI 0.9–1.94), increased FEV(1) decline (−4.5 mL/year; 95% CI −8.6, −0.4) and increased risk of 2+ exacerbations in the previous year (OR 2.6; 95% CI 1.2–6.5). Individuals with GOLD stage 1 had a marginal increase in mortality (HR 1.5; 95% CI 0.93–2.3) but a non-significant impact on FEV(1) decline or exacerbations compared with non-obstructed individuals. CONCLUSIONS: The presence of respiratory symptoms in non-obstructed individuals was a predictor of mortality, lung-function decline and exacerbations, whereas the impact of GOLD stage 1 was mild and inconsistent. Respiratory symptoms were associated with asthma, current smoking, and the report of heart disease. Spirometric case-finding and treatment should target individuals with moderate-to-severe airflow obstruction and those with restriction, the groups with consistent increased mortality.